2022
DOI: 10.1021/acs.analchem.2c00160
|View full text |Cite
|
Sign up to set email alerts
|

Ion Mobility–Mass Spectrometry Reveals the Structures and Stabilities of Biotherapeutic Antibody Aggregates

Abstract: Stability is a key critical quality attribute monitored throughout the development of monoclonal antibody (mAb) therapeutics. Minor changes in their higher order structure (HOS) caused by stress or environment may alter mAb aggregation, immunogenicity, and efficacy. In addition, the structures of the resulting mAb aggregates are largely unknown, as are their dependencies on conditions under which they are created. In this report, we investigate the HOS of mAb monomers and dimers under a variety of forced degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Coupling mass spectrometry with ion mobility for empirical determination of macromolecule cross sections provides a unique opportunity to probe protein structural changes as a function of various experimental parameters and ion internal energies. , For example, dynamic interactions such as allosteric binding effects, structural changes upon drug interactions, and mutant-induced structural aberrations can be studied with ion mobility-mass spectrometry techniques. Gas-phase relative drift times can be converted to averaged collisional cross sections (CCSs) and be used to elucidate protein interactomics and validate protein identities. In addition, the effect of stressors on protein stability and structure, such as gas-phase collisional denaturing via collision-induced unfolding (CIU) interrogation, can provide valuable information about dynamic changes to protein structure beyond what can be discerned from conventional single-energy collision cross section measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Coupling mass spectrometry with ion mobility for empirical determination of macromolecule cross sections provides a unique opportunity to probe protein structural changes as a function of various experimental parameters and ion internal energies. , For example, dynamic interactions such as allosteric binding effects, structural changes upon drug interactions, and mutant-induced structural aberrations can be studied with ion mobility-mass spectrometry techniques. Gas-phase relative drift times can be converted to averaged collisional cross sections (CCSs) and be used to elucidate protein interactomics and validate protein identities. In addition, the effect of stressors on protein stability and structure, such as gas-phase collisional denaturing via collision-induced unfolding (CIU) interrogation, can provide valuable information about dynamic changes to protein structure beyond what can be discerned from conventional single-energy collision cross section measurements.…”
Section: Introductionmentioning
confidence: 99%
“…342 Using fingerprint maps, they were able to isolate one out of the three antigen−antibody complexes that had different binding topology and stability and proved that CIU can be used to classify antigen−antibody complexes based on their epitope maps. 340 Similar to the work cited above, 337 Yuwein et al also used CIU to study a model antibody−biotin conjugate complex and revealed some structural destabilization upon biotin conjugation. 337 Watanabe et al employed CIU to show how domain exchange of an anti-HIV IgG1 mAb is shut down by an engineered mutant.…”
Section: Classical Biophysical Techniques Used To Probe the Stability...mentioning
confidence: 82%
“…Similar to the work cited above, Yuwein et al also used CIU to study a model antibody–biotin conjugate complex and revealed some structural destabilization upon biotin conjugation . Watanabe et al employed CIU to show how domain exchange of an anti-HIV IgG1 mAb is shut down by an engineered mutant .…”
Section: Advanced Im-ms Methods and Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Arrival times may be further converted into rotationally averaged collision cross sections (CCS, Ω), which reflect the three-dimensional conformations of ions in the gas phase. Native IM-MS has been used for the study of the NIST mAb, to assess the influence of mAb (de)­glycosylation, to monitor Fab-arm exchange and bispecific antibody formation, for forced degradation studies, or to measure the drug-to-antibody ratio of ADCs. Native IM-MS thus appears as an attractive technique for the study of biopharmaceuticals, but it is yet to gain popularity in industry …”
Section: Introductionmentioning
confidence: 99%